WORLD EXPERIENCE OF PUBLIC POLICY IN ENSURING ECONOMIC SECURITY OF THE MACHINERY MANUFACTURING SECTOR AND ITS IMPACT ON THE ECONOMY OF FOREIGN COUNTRIES - VDOVENKO, NATALIIA; YATSUN, ANASTASIYA (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is dedicated to examining the main strategic directions for implementing IoT technologies to mechanize and digitalize production processes in the heliciculture sector and analyzing the potential for state support for these developments in Ukraine. In the current conditions of agrarian sector growth, the use of advanced technologies is an essential prerequisite for ensuring economic security. Automating processes in snail production is considered to impact cost optimization, management efficiency, and reduced reliance on human labor, supporting agricultural enterprises' resilience. Existing state support programs for enterprises implementing innovative technologies are analyzed, and it is demonstrated that digitalization and IoT systems significantly improve the efficiency of managing production processes on farms. The article also explores international experience in implementing IoT technologies through examples from leading countries such as Japan, the United States, and Germany. In the U.S., IoT technologies are widely used in the agricultural sector to improve production quality, monitor the health of animals and plants, and reduce losses. American farms actively employ sensor technologies and automated systems that allow farmers to receive real-time data for effective decision-making. Japan excels in integrating IoT systems into production due to its high level of automation and equipment miniaturization, making IoT devices exceptionally accurate and effective even in challenging climatic conditions. Germany, in turn, actively supports the development of IoT for the agricultural sector through state programs and grants to foster agricultural innovation. Specific recommendations for Ukraine are proposed in the article, focusing on creating support mechanisms for heliciculture enterprises to optimize production costs and minimize risks. The experience of leading countries such as the U.S., Japan, and Germany confirms the potential for IoT technology implementation in the development of heliciculture in Ukraine, as it enhances profitability and improves the competitiveness of domestic agribusiness.
Keywords: global experience; state policy; economic security; machine-building complex; snail farming; equipment; agricultural machinery; mechanization; industry; state support; automation